WANPRESTASI DALAM PERJANJIAN TERAPEUTIK DI RUMAH SAKIT UMUM DAERAH (RSUD) DR. MOEWARDI SURAKARTA - , Azka Shovia, S.H ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The research of breach in the therapeutic agreement in Region General Hospital Dr. Moewardi Surakarta aims to determine the forms of default in the therapeutic agreement in Region General Hospital Dr. Moewardi Surakarta and the solution. This research is empirical that is done by direct observation with an in-depth interviews with respondents and informants. The research results are obtained, and then analyzed qualitatively. Presentation of results of research done by connecting the data obtained from the research with theories drawn from the results of normative studies for later delivered, in order to obtain descriptive qualitative description. The result showed that during the period 2007 - 2010 there have been 14 (fourteen) medical dispute cases. In this case, patients may file complaint to the hospital. The forms of these cases include: 2 (two) cases of negligence in medical treatment in the Emergency Unit